2011
DOI: 10.1158/1078-0432.ccr-10-2264
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Endothelin-1 and Endothelin A Receptor Genes and Survival in Patients with Locoregionally Advanced Nasopharyngeal Carcinoma

Abstract: Purpose: We aimed to investigate the prognostic role of endothelin-1 (EDN1) and endothelin A receptor (EDNRA) gene polymorphisms in patients with locoregionally advanced nasopharyngeal carcinoma (NPC).Experimental Design: Two hundred three consecutive patients with locoregionally advanced NPC were enrolled. Seven potentially functional polymorphisms in the EDN1 and EDNRA genes were determined by ligase detection reaction-PCR method from prospectively collected blood samples. The influence of the genetic polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 44 publications
(49 reference statements)
0
11
0
7
Order By: Relevance
“…Endothelin‐1 has various biological functions . The endothelin‐1 system is involved in the regulation of apoptosis, in the autocrine actions (such as proinflammatory, vasoconstrictor, and mitogenic actions), and may contribute to tumor growth and modulate tumor‐host interactions …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelin‐1 has various biological functions . The endothelin‐1 system is involved in the regulation of apoptosis, in the autocrine actions (such as proinflammatory, vasoconstrictor, and mitogenic actions), and may contribute to tumor growth and modulate tumor‐host interactions …”
Section: Discussionmentioning
confidence: 99%
“…7 The endothelin-1 system is involved in the regulation of apoptosis, in the autocrine actions (such as proinflammatory, vasoconstrictor, and mitogenic actions), and may contribute to tumor growth and modulate tumor-host interactions. 20,21 The phenotypic functional role of this polymorphism is not straightforward. Rankinen et al observed a significant effect of the interaction between the genotype and cardiorespiratory fitness level on the risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we selected 18 SNPs from 13 major genes (Table 2). Genotyping of the SNPs was performed by the Shanghai BioWing Applied Biotechnology Company (BioWing, Shanghai, China) using the ligase detection reaction- polymerase chain reaction (LDR-PCR) technique [28,29]. To validate the genotyping results, 10% of the samples were randomly selected for genotyping by a second investigator; the agreement rate was 100%.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Wen et al. investigated EDN1 and the ET A R gene ( EDNRA) polymorphisms in 203 patients with locoregionally advanced NPC by ligase detection reaction PCR. They found that the presence of the EDNRA /H323H polymorphism significantly and independently lowered 5‐year overall survival of patients compared with wild type, whereas EDN1 polymorphisms had no effect.…”
Section: Clinical Opportunitiesmentioning
confidence: 99%